2016
DOI: 10.1039/c6ra14969c
|View full text |Cite
|
Sign up to set email alerts
|

Forced infiltration of silica beads into densely-packed glass fibre beds for thin composite laminates

Abstract: The secondary filler particles were migrated by ultrasonic bubble implosion and microjetting. The migrated fillers facilitated stress transfer among the beads and fibres, and subsequently altered the thermo-mechanical properties to a great extent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…It is also found that CNF/CMC5_1h has more CNFs than CNF/CMC3_1h, following the composition of the deposited cellulose dispersion. In the case of sonication, the sonication generates small vacuum bubbles or voids in the liquid, and the collapse of these cavities then releases high energy, which fragments the cellulose fibers into a small size. , The increasing sonication time makes the cellulose smaller, and consequently, the CNF scatters less light following Rayleigh’s Scattering theory; σ sca ∝ D 3 , where D is the fiber diameter and σ sca is the scattering cross section. ,, The optical properties of our highly transparent and hazy papers are compared with those of the PET film and those reported transparent cellulose-based papers in the literature (Figure c and Table ). Compared with these results, our CNF/CMC papers exhibit competitive or better optical properties.…”
Section: Resultsmentioning
confidence: 94%
“…It is also found that CNF/CMC5_1h has more CNFs than CNF/CMC3_1h, following the composition of the deposited cellulose dispersion. In the case of sonication, the sonication generates small vacuum bubbles or voids in the liquid, and the collapse of these cavities then releases high energy, which fragments the cellulose fibers into a small size. , The increasing sonication time makes the cellulose smaller, and consequently, the CNF scatters less light following Rayleigh’s Scattering theory; σ sca ∝ D 3 , where D is the fiber diameter and σ sca is the scattering cross section. ,, The optical properties of our highly transparent and hazy papers are compared with those of the PET film and those reported transparent cellulose-based papers in the literature (Figure c and Table ). Compared with these results, our CNF/CMC papers exhibit competitive or better optical properties.…”
Section: Resultsmentioning
confidence: 94%